Accountability in global health systems: insights from a network analysis of Purdue Pharmaceuticals - Andrea Bowra; Amaya Perez-Brumer; Lisa Forman; Jillian Clare Kohler (Globalization and Health)
Abstract Beginning in 1996, Purdue Pharmaceuticals (Purdue) knowingly mislabeled and mass marketed OxyContin (oxycodone), an opioid painkiller, catalyzing the opioid crisis which has been responsible for more than 600 000 deaths in and beyond North America. This case is an extreme example of how transnational pharmaceutical companies prioritize shareholder profits over public wellbeing. As such, the field of global health faces the critical challenge of better understanding how transnational pharmaceutical companies, like Purdue, can be held to account for the harms they cause. Within the framework of Actor-Network Theory, a sociomaterial approach to analyzing complex networks, this case study uses key informant interviews (n = 18) to examine how accountability is taken up in and by global health systems in response to the harms caused by Purdue. Findings highlight the multiple co-existing versions of accountability enacted within global health systems organized as three separate but interrelated networks: social accountability, political accountability, and legal accountability. Though often interconnected, these diverse networks mobilized distinct tools, resources, and strategies, such as news articles, scholarly literature, and policy guidelines, to construct and stabilize enactments of accountability. Through this in-depth examination of the complex interactions involved in global health and pharmaceutical systems, this study offers a nuanced understanding of the diverse actors mobilized and the unique strengths leveraged within and by accountability networks. Further, in examining these networks’ differences, interconnectedness, and peculiarities, we broaden the scope of how accountability is defined, conceptualized, and operationalized in global health systems.